Melanogenic Difference Consideration in Ethnic Skin Type: A Balance Approach Between Skin Brightening Applications and Beneficial Sun Exposure - Markiewicz E; Idowu OC (Dove Medical Press, 2020)
Ewa Markiewicz, Olusola Clement Idowu Hexis Lab Limited, The Core, Newcastle Helix, Newcastle Upon Tyne NE4 5TF, UKCorrespondence: Olusola Clement IdowuHexis Lab, Newcastle Helix, The Core, Bath Lane, Newcastle Upon Tyne NE4 5TF, UKTel +44 191 495 7311Email sola@hexislab.comAbstract: Human skin demonstrates a striking variation in tone and color that is evident among multiple demographic populations. Such characteristics are determined predominantly by the expression of the genes controlling the quantity and quality of melanin, which can alter significantly due to the presence of small nucleotide polymorphism affecting various steps of the melanogenesis process and generally linked to the lighter skin phenotypes. Genetically determined, constitutive skin color is additionally complemented by the facultative melanogenesis and tanning responses; with high levels of melanin and melanogenic factors broadly recognized to have a protective effect against the UVR-induced molecular damage in darker skin. Long-term sun exposure, together with a genetic makeup responsible for the ability to tan or the activity of constitutive melanogenic factors, triggers defects in pigmentation across all ethnic skin types. However, sun exposure also has well documented beneficial effects that manifest at both skin homeostasis and the systemic level, such as synthesis of vitamin D, which is thought to be less efficient in the presence of high levels of melanin or potentially linked to the polymorphism in the genes responsible for skin darkening triggered by UVR. In this review, we discuss melanogenesis in a context of constitutive pigmentation, defined by gene polymorphism in ethnic skin types, and facultative pigmentation that is not only associated with the capacity to protect the skin against photo-damage but could also have an impact on vitamin D synthesis through gene polymorphism. Modulating the activities of melanogenic genes, with the focus on the markers specifically altered by polymorphism combined with differential requirements of sun exposure in ethnic skin types, could enhance the applications of already existing skin brightening factors and provide a novel approach toward improved skin tone and health in personalized skincare.Keywords: ethnic skin types, melanogenesis, hyper-pigmentation, vitamin D